SmartONE: Desenvolvimento de novas interfaces para a plataforma buildONE - Tiago Miguel da Cunha Gomes (2013)
buildONE is a software platform designed to manage work systems that contain activities with a different structural organization, like projects, workflow processes, or even emerging semi-structured processes with a strong human component. In addiction to supporting work management, this platform also includes a set of features and tools to support document and communication management. All information resources managed by the application are stored in central repositories. The main goal of this dissertation is develop a new set of interfaces to the buildONE platform. This way, users can access available resources from buildONE using productivity tools, like Microsoft Outlook or a Desktop application integrated with Windows Explorer. For this it is intended to specify and implement an API using Web Services that gives acess to the resources managed by buildONE platform. This application is developed using the SharePoint platform and the resouces can be documents or information stored in central repositories. Thus, it will be possible to use these resources in other platforms, such as those available on mobile devices or in other operating systems. In order to validate the obtained results, a new module to the buildONE application was implemented: the Work orders management module. In this module, the integration mechanisms developed during this project are extensively used.